The Impact Of Means Of Support On The Intention Entrepreneurial Field Research On A Sample Of Algerian Students - عياد, صالح; قالون, جيلالي; عينوس, رضوان (Journal of Economics and Administrative Sciences, 2019)
The aim of this paper to study the effect of the implicit factors on the entrepreneurial spirit of the students of the Algerian university. Our structural model was proposed based on the model (Shapiro et Sokol, 1982) and the model (Ajzen, 1991). We tested it on a sample of 163 university students at the University of Algiers 3. The model consists of a set of variables (the intention of contracting as a dependent variable, structural and social educational support as independent variables). The results showed that educational and social support factors affect the entrepreneurial spirit of students more than structural support. The Applied Impacts are the enhancing of knowledge capacities of university students will contribute to reducing the causes of organizational failures of their businesses, thereby increasing their competitiveness and making them a tool for national productivity, not to mention important jobs. So, the Value of this is an Authenticity of research enriches the literature of knowledge management and construction that contribute to the search for how to support investment and support the entrepreneurial spirit, especially among young people through many mechanisms and means of support